Phenotyping an adult zebrafish lamp2 cardiomyopathy model identifies mTOR inhibition as a candidate therapy. (August 2019) - Dvornikov, Alexey V.; Wang, Mingmin; Yang, Jingchun; Zhu, Ping; Le, Tai; Lin, Xueying; Cao, Hung; Xu, Xiaolei
Abstract: Adult zebrafish is an emerging vertebrate model for studying genetic basis of cardiomyopathies; but whether the simple fish heart can model essential features of hypertrophic cardiomyopathy (HCM) remained unknown. Here, we report a comprehensive phenotyping of a lamp2 knockout (KO) mutant. LAMP2 encodes a lysosomal protein and is a causative gene of Danon disease that is characterized by HCM and massive autophagic vacuoles accumulation in the tissues. There is no effective therapy yet to treat this most lethal cardiomyopathy in the young. First, we did find the autophagic vacuoles accumulation in cardiac tissues from lamp2 KO. Next, through employing a set of emerging phenotyping tools, we revealed heart failure phenotypes in the lamp2 KO mutants, including decreased ventricular ejection fraction, reduced physical exercise capacity, blunted β-adrenergic contractile response, and enlarged atrium. We also noted changes of the following indices suggesting cardiac hypertrophic remodeling in lamp2 KO: a rounded heart shape, increased end-systolic ventricular volume and density of ventricular myocardium, elevated actomyosin activation kinetics together with increased maximal isometric tension at the level of cardiac myofibrils. Lastly, we assessed the function of lysosomal-localized mTOR on the lamp2 -associated Danon disease. We found that haploinsufficiency of mtor was able to normalize some characteristics of the lamp2 KO, including ejection fraction, β-adrenergic response, and the actomyosin activation kinetics. In summary, we demonstrate the feasibility of modeling the inherited HCM in the adult zebrafish, which can be used to develop potential therapies. Graphical abstract: Unlabelled Image Highlights: Zebrafish has a single LAMP2 homologue. Loss-of-function of lamp2 in zebrafish models human Danon disease Both metabolic abnormality and cardiac dysfunction are recapitulated. mtor inhibition attenuates cardiac dysfunction while metabolic abnormality persists.